MUC5B modulation of early oral biofilm glucose metabolism - Robertsson, Carolina; Davies, Julia; Svensäter, Gunnel; Nord, Anders Bay; Norrström, Niclas; Wickström, Claes (Frontiers in Oral Health, 2025)
IntroductionSalivary mucin MUC5B has been suggested to support eubiosis in early oral biofilms by regulating the attachment of commensals, while downregulating dysbiotic activities related to dental caries development, such as microbial carbohydrate transport and metabolism.MethodsTo investigate how the metabolism of glucose, a potential driver for dental caries, in early mono- and dual-species biofilms of oral Actinomyces naeslundii and Streptococcus gordonii clinical isolates was affected by the presence of the complex salivary mucin MUC5B, this study employed nuclear magnetic resonance (NMR)-based metabolomics with the interpretation of network integration.Results and discussionMUC5B reduced early attachment in the presence of glucose compared with uncoated surfaces but maintained even species distribution. This suggests that MUC5B may represent an innate mechanism to regulate biofilm eubiosis by supporting early coadhesion while regulating total biomass. All annotated metabolites were intermediates in either carbohydrate metabolism, pyruvate conversion, or amino acid metabolism, which was not unexpected in biofilm glucose metabolomes from two saccharolytic species since pyruvate conversion represents a junction point between glycolysis and amino acid metabolic chains. The 10 metabolites present in all early biofilms represent a core metabolome shared by A. naeslundii and S. gordonii. Such core metabolomes can be used to detect deviations in future studies. Significant differences in metabolite abundance elicited by the presence of MUC5B were also detected. In early biofilms where they were each present, pyruvate, ethanol, and metabolite 134 were present in significantly higher abundance in the presence of 25% MUC5B with 20 mM glucose (MUC5B + G) compared with a physiologic buffer with 20 mM glucose (PBS + G), while metabolites 84, 97, and sarcosine were present at significantly lower abundance. Metabolite 72 was unique to biofilms grown in MUC5B + G, and eight unannotated metabolites were unique to biofilms grown in PBS + G. A pathway enrichment analysis of the metabolites that were differently expressed in early A. naeslundii, S. gordonii, and dual-species biofilms grown with 20 mM glucose with or without MUC5B showed that pyruvate metabolism was significantly over-represented. Studying the metabolic interactions between commensal members of oral biofilms and modulatory effects of host factors such as glycoproteins in saliva during the metabolism of substrates that are potential drivers of dysbiosis, such as glucose, is essential to understand the roles of oral microbial ecosystems in oral health and disease.